Factors affecting reorientation of hydraulically induced fracture during fracturing with oriented perforations in shale gas reservoirs - Qing-Chao Li; Liang Zhou; Zhi-Min Li; Zhen-Hua Liu; Yong Fang; Lei Zhao; Ying Han (Fracture and Structural Integrity)
Hydraulic fracturing with oriented perforations is an effective technology for gas development from shale reservoirs. However, fracture reorientation during fracturing operation can affect the fracture conductivity and hinder the effective production of shale gas. In addition, factors such as perforation azimuth, in-situ stresses, fracturing fluid viscosity and injection rate can affect fracture reorientation during fracturing operation, and the first three factors are controllable factors. In the present work, a numerical simulation model for investigating fracture reorientation during fracturing with oriented perforations was established, and it was verified to be suitable for all investigations in this paper. Based on this simulation model, factors affecting both initiation and reorientation of the hydraulically induced fractures were investigated. The investigation results show that the fluid viscosity has little effect on initiation pressure of hydraulically induced fracture during fracturing operation, and the initiation pressure is mainly affected by perforation azimuth, injection rate and the stress difference. Moreover, the investigation results also show that perforation azimuth and difference between two horizontal principal stresses are the two most important factors affecting fracture reorientation. Based on the investigation results, the optimization of fracturing design can be achieved by adjusting some controllable factors. However, the regret is that the research object herein is a single fracture, and the interaction between fractures during fracturing operation needs to be further explored